(untitled) (Research Nepal Journal of Development Studies, 2023)
Tourism is an applicable tool of community development through the women empowerment. The development of tourism in a specified community zone empowers the people from social, economic, political, and psychological dimensions. The paper aims to identify tourism as a tool of women empowerment in community development. To identify tourism as a tool to women empowerment it needs in-depth analysis of issues from intense literature review. It is an intense review of the study on, Tourism as a Tool of Women Empowerment: A General Review. In conclusion, the study identify tourism can be a perfect or a complete tool of women empowerment in any specified community. The identity of the community, culture of hospitality, rites and rituals, household prayers and worship, and livelihood strategies, are the main tourism attractions, in every household is led by women in most of the society.